Persistence, Magnitude, and Patterns of Postacute Symptoms and Quality of Life Following Onset of SARS-CoV-2 Infection: Cohort Description and Approaches for Measurement. (21st December 2021) - Peluso, Michael J; Kelly, J Daniel; Lu, Scott; Goldberg, Sarah A; Davidson, Michelle C; Mathur, Sujata; Durstenfeld, Matthew S; Spinelli, Matthew A; Hoh, Rebecca; Tai, Viva; Fehrman, Emily A; Torres, Leonel; et al.
Abstract: Background: There is mounting evidence for the presence of postacute sequelae of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (PASC), but there is limited information on the spectrum, magnitude, duration, and patterns of these sequelae as well as their influence on quality of life. Methods: We assembled a cohort of adults with a documented history of SARS-CoV-2 RNA positivity at ≥2 weeks past onset of coronavirus disease 2019 (COVID-19) symptoms or, if asymptomatic, first positive test. At 4-month intervals, we queried physical and mental health symptoms and quality of life. Results: Of the first 179 participants enrolled, 10 were asymptomatic during the acute phase of SARS-CoV-2 infection, 125 were symptomatic but not hospitalized, and 44 were symptomatic and hospitalized. During the postacute phase, fatigue, shortness of breath, concentration problems, headaches, trouble sleeping, and anosmia/dysgeusia were most common through 8 months of observation. Symptoms were typically at least somewhat bothersome and sometimes exhibited a waxing-and-waning course. Some participants experienced symptoms of depression, anxiety, and post-traumatic stress, as well as difficulties with performance of usual activities. The median visual analogue scale rating of general health was lower at 4 and 8 months compared with pre-COVID-19. Two clusters of symptom domains were identified. Conclusions: Many participants report bothersome symptoms following onset of COVID-19 with variable patterns of persistence and impact on quality of life. The substantial variability suggests the existence of multiple subphenotypes of PASC. A rigorous approach to the prospective measurement of symptoms and functional manifestations sets the stage for the next phase of research focusing on the pathophysiologic causes of the various subgroups of PASC.